Cardiovascular drugs in human mechanical nociception: digoxin, amlodipine, propranolol, pindolol and atenolol. - Alfredo Del Giaccio, Alfredo Del Giaccio; Eblen Zajjur, Antonio (Investigación Clínica, 2013)
Â  Calcium channel blockers, Î² adrenergic receptor blockers and Na/K ATPase inhibitors are widely used drugs, mainly for cardiovascular diseases. Their pharmacological targets are not restricted to the cardivascular tissue, nociceptive system structures also express similar targets, which strongly suggests a direct effect on pain sensation. To evaluate the pain intensity changes in outpatient groups, who receive these drugs as a therapy, a cross-sectional sampled, randomized patient groups receiving the calcium channel blocker amlodipine for blood hypertension (n=45), Î² adrenergic receptor blockers (propranolol, atenolol or pindolol; n=40) for blood hypertension, or digoxin (n=40) for heart failure, were compared to an aparently healthy volunteers control group (n=60). A calibrated noxious pressure of 890 g/mm2 was applied for 5 seconds on the patient”™s sternum. Subjective pain intensity was reported by the visual analog scale (VAS, 0 to 10). Pain modulation system was evaluated by the application of a second stimulus with a 5 minutes delay. The analgesic effect of the Î² blockers group (propanolol, atenolol, pindolol) was dosage-dependant (”“36.8%; P=0.0000003), without differences among them. The calcium channel blocker amlodipine showed lower pain scores (”“50.6%; P=0.0000003) than Î²-receptor blockers (P=0.0000003). Digoxin presented the highest pain scores (+56.5%; P=0.0000003). All pain scores for the second stimulus were lower than the first stimulus and were differentially affected by Î²-blockers (atenolol, pindolol and propanolol) and calcium channel blocker (amlodipine), but not by digoxin. These results suggest the influence of widely clinically used cardiovascular drugs on nociception.